1994
DOI: 10.1071/pp9940079
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Growth Reduction in Elongating and Expanding Leaf Tissue of Sugarcane Under Saline Conditions

Abstract: Plants of sugarcane, cv. Co 1148, were subjected to salinisation with 200 milliequivalents L-1 of Cl- -type salts mixture (having Na+, Ca2+ and Mg2+ as 3 :1:1 and Cl- and SO42- as 4:1 on a milli- equivalent basis) for two weeks or more during the tillering phase. Soluble sugar concentrations increased by 55% in the blades of recently matured leaves (source tissues) and by nearly 225% in the elongating sheath bases (sink tissues) as a result of salinisation. Leaf elongation within 3 h of desalin- isation was mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
6
0
4
Order By: Relevance
“…In vitro culture technique provides a controlled and uniform environment for studying the physiological effects of salt and dehydration stress at the cellular (Ahmad et al 2007) as well as plant level (Lokhande et al 2011). Therefore, besides understanding the effects of salt and dehydration stress at the whole plant level ex vitro (Kumar et al 1994;Wahid et al 1997;Wahid 2004;Patade et al 2011), attempts are being made to study the in vitro cellular or tissue levels stress responses (Cui et al 2010;Lokhande et al 2010;Pan et al 2010;Sun et al 2010). Studies with non-halophytes have shown that degree of salt tolerance observed in the whole plant is also exhibited in callus tissues suggesting that salt tolerance mechanisms also operate at cellular level (Arzani 2008;Xu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro culture technique provides a controlled and uniform environment for studying the physiological effects of salt and dehydration stress at the cellular (Ahmad et al 2007) as well as plant level (Lokhande et al 2011). Therefore, besides understanding the effects of salt and dehydration stress at the whole plant level ex vitro (Kumar et al 1994;Wahid et al 1997;Wahid 2004;Patade et al 2011), attempts are being made to study the in vitro cellular or tissue levels stress responses (Cui et al 2010;Lokhande et al 2010;Pan et al 2010;Sun et al 2010). Studies with non-halophytes have shown that degree of salt tolerance observed in the whole plant is also exhibited in callus tissues suggesting that salt tolerance mechanisms also operate at cellular level (Arzani 2008;Xu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane is a glycophyte; reported to be salt sensitive; and exhibits toxicity symptoms, low sprout emergence, nutritional imbalance, and overall growth reduction leading to low biomass (Wahid 2004). Salinity effects on sugarcane have been studied at the physiological level (Kumar et al 1994;Wahid et al 1997;Wahid 2004;Patade et al 2008). Errabii et al (2007) has analyzed effects of salt and mannitol stress on sugarcane calli in relation to growth, ions, and proline concentrations.…”
mentioning
confidence: 99%
“…However, Naidoo et al (2004) did not report any clear trend in carbon assimilation or gas exchange parameters despite significant reduction in biomass occurring in all salt-stressed varieties tested. Salt stress reportedly increased soluble sugars in the leaf sheaths of sugarcane, possibly due to reduced sink strength (Kumar et al 1994).…”
Section: Salinity Stressmentioning
confidence: 99%